KEMAMPUAN FAKTOR AKUNTANSI DAN NON AKUNTANSI DALAM MEMPREDIKSI BOND RATING - Rusfika, Rusfika; Wahidahwati, Wahidahwati (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to find out the ability of accounting and non-accounting factor in predicting the bond rating to the non-finance companies. The samples are non-finance companies which are listed in Indonesia Stock Exchange (IDX) during 2010-2013 periods which are rated by PT.Pefindo. The samples of the research have been selected by using purposive sampling method. 48 samples of bonds with 192 pooling of 16 companies have been obtained. Hypothesis test has been done by using logistic regressions analysis. Based on the result of the logistic regressions analysis with its significance level is 5% has proven that: 1) Profitability, solvability, liquidity and bail bond have positive and significant influence to the bond rating, 2) Productivity, bond age and auditorâs reputation have insignificant influence to the bond rating. Â Keywords: Bond Rating, Accounting Factor, Non-Accounting FactorÂ